Spontaneous behaviors of post-orchiectomy pain in horses regardless of the effects of time of day, anesthesia, and analgesia - Trindade, Pedro Henrique Esteves [UNESP]; Taffarel, Marilda Onghero; Luna, Stelio Pacca Loureiro [UNESP] (MDPI, 2021)
This prospective and longitudinal study aimed to identify spontaneous post-orchiectomy pain behaviors in horses regardless of the effects of anesthesia, analgesia, and recording time of day. Twenty-four horses divided into four groups were submitted to: inhalation anesthesia only (GA), or combined with previous analgesia (GAA), or orchiectomy under pre (GCA), or postoperative (GC) analgesia. The data obtained from the subtraction of frequency and/or duration of 34 behaviors recorded during seven 60-min time-points in the 24 h after the anesthesia from those recorded in the mirrored time-points in the 24 h before the anesthesia (delta) were compared over time and among groups by Friedman and Kruskal–Wallis tests, respectively (p < 0.05). Time of day influenced the behaviors of walk, look out the window, rest the pelvic limb, and rest standing still. The only pain-related behaviors were decreased mirrored proportional differences in time spent drinking, and eating, and increased mirrored proportional differences in the frequency or duration of look at the wound, retract the pelvic limb, expose the penis, and look at the back of the stall. In conclusion, confounding factors rather than pain may influence several suggestive pain-related behaviors documented in the literature.
Keywords: Animal welfare; Horses; Pain measurement